On the largest component of subcritical random hyperbolic graphs - Diel, Roland; Mitsche, Dieter (Electronic communications in probability, 2021)
We consider the random hyperbolic graph model introduced by [KPK + 10] and then formalized by [GPP12]. We show that, in the subcritical case α > 1, the size of the largest component is n^{1/(2α)+o(1)} , thus strengthening a result of [BFM15] which gave only an upper bound of n^{1/α+o(1)}.